Influence of Convection Heat Transfer of Tread Plate in Polar Environment - HAN Xueyang, WU Lin, LIU Zhibing, YU Dongwei, KONG Xiangyi, ZHANG Dayong (Shanghai Jiaotong Daxue xuebao)
To solve the problem of cold protection for marine equipment against cold caused by the harsh polar environment, electrical tracing is commonly used in engineering. In this paper, numerical simulation and experimental methods are used to analyze the influencing factors of thermal balance of electric heat tracing tread plate components in typical polar environment with wind speed ranging from 0 to 40 m/s and temperature ranging from -40 ℃ to 0 ℃. Based on numerical simulation and experimental test, the convective heat transfer coefficient of electric heating tread plate components at different wind speeds and temperatures is obtained. The results show that increasing wind speed and decreasing temperature will increase the convective heat transfer coefficient of the tread plate. Wind speed is the main factor affecting the heat transfer of the tread plate, while temperature has little effect. Finally, based on the experimental data and the classical theory of convective heat transfer of plate components, a prediction model of convective heat transfer coefficient of electric heating tread plate components is established, and the correctness of the model is verified by numerical simulation.